2016
DOI: 10.1007/s00417-016-3400-4
|View full text |Cite
|
Sign up to set email alerts
|

Intolerant contact lens wearers exhibit ocular surface impairment despite 3 months wear discontinuation

Abstract: Ocular surface parameters were altered in intolerant CL wearers, even after a prolonged discontinuation period. Our data suggest that OS recovery necessary to successfully refit lenses may need a discontinuation time longer than 3 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…23,36 This issue as it relates to contact lens dropout has been specifically analyzed by Giannaccare et al (2016) via a retrospective analysis (n = 87). 37 The authors found that compared to controls, subjects who had discontinued contact lens wear had lower/worse tear break up time and Schirmer test values, and higher/worse ocular surface disease index (OSDI) and corneal staining scores. These results suggest that patients with signs of dry eye such as quick tear film evaporation, poor tear production, and corneal irritation may be more likely to drop out of contact lenses.…”
Section: Ocular Surface Factorsmentioning
confidence: 98%
“…23,36 This issue as it relates to contact lens dropout has been specifically analyzed by Giannaccare et al (2016) via a retrospective analysis (n = 87). 37 The authors found that compared to controls, subjects who had discontinued contact lens wear had lower/worse tear break up time and Schirmer test values, and higher/worse ocular surface disease index (OSDI) and corneal staining scores. These results suggest that patients with signs of dry eye such as quick tear film evaporation, poor tear production, and corneal irritation may be more likely to drop out of contact lenses.…”
Section: Ocular Surface Factorsmentioning
confidence: 98%
“…First reported in human serum and later in other body fluids, ZAG-2 represents an interesting protein that stimulates lipid breakdown in adipocytes, and which is highly expressed in cancer cachexia [52]. A reduction of ZAG-2 tear levels was documented in CL wearers [53], DED [27,54], fungal infections at an early stage [55][56][57], diabetic patients [58], and an increase in tears of smokers and patients with Grave's ophthalmopathy [59]. The function of ZAG-2 in tears and its possible role in lipid degradation has been postulated but not demonstrated [59].…”
Section: Discussionmentioning
confidence: 95%
“…Recently, substance P, a molecule involved in the transmission of pain has been shown to be higher in symptomatic contact lens wearers [439]. This finding is of particular interest, given reports of alterations to corneal and conjunctival sensitivity to mechanical and cold stimuli amongst dropouts from contact lens wear, compared to healthy matched controls [430], and in symptomatic versus asymptomatic habitual contact lens wearers [429], respectively. Increased tortuosity of nerve fibres in the central cornea is associated with higher ocular symptoms [440].…”
Section: Patient-related Risk Factorsmentioning
confidence: 94%
“…Reduced tear film stability in terms of shorter non-invasive [384,428] and invasive tear film breakup time (TBUT) [381,429], higher tear film evaporation rate and thinner lipid layer thickness [388] have been associated with discomfort in symptomatic contact lens wearers. Furthermore, reduced non-invasive pre-contact lens thinning time has been associated with symptoms [387], and dropouts from contact lens wear displayed shorter invasive TBUT 3 months after discontinuation compared to matched controls [430]. Conversely, other studies have shown no association between non-invasive TBUT, tear volume (phenol red thread test) and comfort in subjects fitted with SiHy contact lenses [407], or when comparing dropouts to successful contact lens wearers [431].…”
Section: Patient-related Risk Factorsmentioning
confidence: 99%